Q Wave in the Inferior Leads: There Is More Than Scar. Issue 6 (28th January 2015) - Bogossian, Harilaos; Ninios, Ilias; Frommeyer, Gerrit; Mijic, Dejan; Hasan, Fuad; Bandorski, Dirk; Eckardt, Lars; Lemke, Bernd; Zarse, Markus
Abstract : Q waves can regularly be observed in the 12‐lead electrocardiogram either due to heart axis underlying pathology such as subacute myocardial infarction, myocardial scar, or accessory pathways. Rarely, other entities such as circumscribed hypertrophy can induce significant Q wave and represent an important differential diagnosis especially in younger patients. In the setting of atypical chest pain determination of the correct diagnosis can be challenging. Therefore, circumscribed hypertrophy should be taken into account to avoid unnecessary invasive procedures.